2006
DOI: 10.3168/jds.s0022-0302(06)72406-7
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Trait Loci Affecting Fertility and Calving Traits in Swedish Dairy Cattle

Abstract: Impaired fertility is the main reason for involuntary culling of dairy cows in Sweden. The objective of this study was to map quantitative trait loci (QTL) influencing fertility and calving traits in the Swedish dairy cattle population. The traits analyzed were number of inseminations, 56-d nonreturn rate, interval from calving to first insemination, fertility treatments, heat intensity score, stillbirth, and calving performance. A genome scan covering 20 bovine chromosomes was performed using 145 microsatelli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
55
3
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(68 citation statements)
references
References 18 publications
8
55
3
1
Order By: Relevance
“…Although not all studies have documented significant associations with different measures of reproductive performance on either BTA 2 or BTA 21 (Holmberg and Andersson-Eklund, 2006;Pryce et al, 2010), significant associations with SNPs on BTA 2 and BTA 21 have been reported in some studies (Huang et al, 2010;Sahana et al, 2010;Schulman et al, 2011). Of particular note were the two SNPs, ARS-BFGL-NGS-36151 and BTB-00117780, reported by Huang et al (2010) on BTA 2 to be associated with fertilisation rate in a Holstein population independent to that used in the present study.…”
Section: Genetic Parameterscontrasting
confidence: 42%
See 2 more Smart Citations
“…Although not all studies have documented significant associations with different measures of reproductive performance on either BTA 2 or BTA 21 (Holmberg and Andersson-Eklund, 2006;Pryce et al, 2010), significant associations with SNPs on BTA 2 and BTA 21 have been reported in some studies (Huang et al, 2010;Sahana et al, 2010;Schulman et al, 2011). Of particular note were the two SNPs, ARS-BFGL-NGS-36151 and BTB-00117780, reported by Huang et al (2010) on BTA 2 to be associated with fertilisation rate in a Holstein population independent to that used in the present study.…”
Section: Genetic Parameterscontrasting
confidence: 42%
“…Several other studies have attempted to locate genomic regions associated with reproductive performance in cattle (Holmberg and Andersson-Eklund, 2006;Huang et al, 2010;Pryce et al, 2010;Sahana et al, 2010;Schulman et al, 2011). Although not all studies have documented significant associations with different measures of reproductive performance on either BTA 2 or BTA 21 (Holmberg and Andersson-Eklund, 2006;Pryce et al, 2010), significant associations with SNPs on BTA 2 and BTA 21 have been reported in some studies (Huang et al, 2010;Sahana et al, 2010;Schulman et al, 2011).…”
Section: Genetic Parametersmentioning
confidence: 99%
See 1 more Smart Citation
“…Several recent studies taking into account fertility parameters alongside other production traits illustrate this point (Kirkpatrick et al, 2000;Lien et al, 2000;Boichard et al, 2003;Ashwell et al, 2004;Schnabel et al, 2005). To the best of our knowledge, only four studies in cattle focused exclusively on fertility traits (Holmberg and Andersson-Eklund, 2006;Guillaume et al, 2007;Holmberg et al, 2007;Schulman et al, 2008), while the other studies involve the phenotyping of other production traits. Loci involved mainly in female fertility were identified (see Table 1).…”
Section: Experimental Models For a Better Understanding Of Fertility mentioning
confidence: 95%
“…Calf mortality (stillbirth) as a maternal trait has been previously mapped by Holmberg and Andersson-Eklund [15] and Kühn et al [24]. QTL were suggested on BTA4 and 19 and detected at genome-wise significance on BTA7 and 11 [15] and BTA8, 10, 18, and X/Y [24].…”
mentioning
confidence: 98%